Flexor Hallucis Longus tendon rupture in RA-patients is associated with MTP 1 damage and pes planus - Buurke Jaap J; Dubbeldam Rosemary; Drossaers-Bakkers Wiepke K; Baan Henriette; Nene Anand; van de Laar Martin AFJ (BMC Musculoskeletal Disorders, 2007)
Abstract Background To assess the prevalence of and relation between rupture or tenosynovitis of the Flexor Hallucis Longus (FHL) tendon and range of motion, deformities and joint damage of the forefoot in RA patients with foot complaints. Methods Thirty RA patients with painful feet were analysed, their feet were examined clinically for the presence of pes planus and range of motion (ROM), radiographs were scored looking for the presence of forefoot damage, and ultrasound examination was performed, examining the presence of tenosyovitis or rupture of the FHL at the level of the medial malleolus. The correlation between the presence or absence of the FHL and ROM, forefoot damage and pes planus was calculated. Results In 11/60(18%) of the feet, a rupture of the FHL was found. This was associated with a limited motion of the MTP1-joint, measured on the JAM (χ2 = 10.4, p = 0.034), a higher prevalence of pes planus (χ2 = 5.77, p = 0.016) and a higher prevalence of erosions proximal at the MTP-1 joint (χ2 = 12.3, p = 0.016), and joint space narrowing of the MTP1 joint (χ2 = 12.7, p = 0.013). Conclusion Rupture of the flexor hallucis longus tendon in RA-patients is associated with limited range of hallux motion, more erosions and joint space narrowing of the MTP-1-joint, as well as with pes planus.